Baseline CD4 and mortality trends in the South African human immunodeficiency virus programme: Analysis of routine data - Lilian, Rivka R. (South Afr J HIV Med, 2019)
BACKGROUND: Despite widespread availability of antiretroviral therapy (ART) in South Africa, there remains a considerable burden of human immunodeficiency virus (HIV)-related morbidity and mortality. OBJECTIVES: To describe ART initiation and outcome trends over time, with a focus on clients presenting with advanced HIV-infection, so as to identify interventions to reduce morbidity and mortality. METHODS: Routine TIER.Net data from HIV-infected adults who had a documented baseline CD4 count and were newly initiating ART in Johannesburg or Mopani districts from 2004 to 2017 were analysed. Trends in baseline CD4 count and 5-year mortality were investigated and the population initiating ART with CD4 < 200 cells/mm(3) was described. RESULTS: The Johannesburg and Mopani data sets comprised 203 131 and 101 814 records, respectively. Although median CD4 count increased over time, the proportion of initiations at CD4 < 200 cells/mm(3) in 2017 remained high (Johannesburg 39%, Mopani 35%). Mortality was significantly increased among clients with CD4 < 200 compared to those with higher baseline counts (p < 0.001). Even though mortality among clients with low CD4 declined over time, likely because of improved drug regimens, in 2016–2017 mortality was still significantly increased among these clients (p < 0.001). Delivery of cotrimoxazole prophylaxis to clients with low CD4 declined over time to < 30% in 2017 and was associated with clinical stage. Presentation with CD4 < 200 cells/mm(3) was associated with older age, male gender and hospitalisation. CONCLUSION: A concerningly large proportion of South Africans still initiate ART at low CD4 counts. This is associated with increased mortality and requires targeted interventions to improve delivery of prophylactic regimens and early engagement in care.